Summary of Research and Development of Reservoir Pore Structure - Zhang, Yihao (Scientific Journal of Technology, 2025)
As an important index of rock internal space characteristics, reservoir pore structure directly affects oil and gas storage capacity and seepage efficiency, and is a key factor in the exploration and development of unconventional oil and gas resources such as shale gas and tight oil. In recent years, with the advancement of unconventional oil and gas exploration to deep and ultra-deep layers, the study of reservoir pore structure has shown a development trend from qualitative analysis to quantitative characterization, from two-dimensional observation to three-dimensional reconstruction, and from single-technology characterization to full-aperture joint characterization. This paper systematically reviews the content evolution of reservoir pore structure research, the development of characterization technology, joint characterization methods and the research focus of different reservoirs, analyzes the existing problems and looks forward to the future research direction, in order to provide theoretical reference for reservoir evaluation and efficient development.